The Effect of the Unique Features of Y Generation on Organizational Commitment / Y Kuşağının Belirleyici Özelliklerinin Örgütsel Bağlılık Üzerindeki Etkisi - Civelek, Mustafa Emre; Çemberci, Murat; Aşçı, Mehmet Saim; Öz, Sabri (Journal of History Culture and Art Research, 2017)
ABSTRACT In this research, the determinants of the generations and unique characteristics of Generation Y are examined and the effect of this unique characteristics on organizational commitment is investigated. In the introduction part of the research, different features separating the generations from each other were mentioned and the studies done in this subject were examined and the studies and findings of different researchers were evaluated. In the final part of the survey, there is the analysis result of the survey collected from overall Turkey from 8 corporations. Sample size of this research is 267. In order to measure organizational commitment, the scale developed by Allen and Meyer was used (Allen & Meyer, 1993). In order to measure team working, the scale developed by Levi and Slem was used (Levi & Slem, 1995). In order to measure playful spirit at work, the scale developed by Berg was used (Berg, 2011). According to the test results, there is a positive and significant relationship between Workplace fun and Team Working and between Team Working and Organizational Commitment. Contrary to expectation, there is not directly relation between organizational commitment and workplace fun. But work place fun positively effects organizational commitment through team working indirectly. The results of this research are to confirm that employees will be more likely to work in teams if organization environments are established to make them happy and entertained, thereby increasing their organizational commitment. ÖZ Bu araştırmada Kuşakların belirleyici özellikleri incelenerek Y kuşağını diğer kuşaklardan ayıran özelliklerin neler olduğu ve bu özelliklerin örgütsel bağlılık üzerinde ne gibi bir etkisi olduğu araştırılmaktadır. Araştırmanın giriş kısmında kuşakları birbirinden ayrıştıran farklı özelliklere değinilmiş ve bu konuda yapılan çalışmalar incelenerek farklı araştırmacıların çalışma ve tespitleri değerlendirilmiştir. Araştırmanın son bölümünde, Türkiye genelinde Y kuşağının örgütsel bağlılık düzeylerini ölçmek üzere 8 kurumda 267 kişiye uygulanan araştırmanın analiz sonuçları bulunmaktadır. Örgütsel bağlılık düzeyini ölçmek için Allen and Meyer tarafından geliştirlen ölçek kullanılmıştır.Takım çalışmasına yatkınlık düzeyini ölçmek için Levi and Slem tarafından geliştirilen ölçek kullanılmıştır. Eğlenerek çalışma isteğini ölçmek için Berg tarafından geliştirilen ölçek kullanılmıştır. Hipotez testi sonuçlarına göre, eğlenerek çalışma ile takım çalışması arasında ve takım çalışması ile örgütsel bağlılık arasında pozitif ve anlamlı bir ilişki bulunmuştur. Beklenenin aksine, örgütsel bağlılık ile eğlenerek çalışma arasında doğrudan bir ilişki bulunamamıştır. Ancak, eğlenerek çalışma takım çalışması aracılığıyla dolaylı olarak örgütsel bağlılığı olumlu yönde etkiler. Bu araştırmanın sonuçlarına göre, çalışanlar örgüt ortamı daha eğlenci olduğunda takım çalışmasına daha yatkın olmaktadırlar.